The Effect of Using Padlet in Think-Pair-Share Strategy on EFL Senior High School Students’ Reading Comprehension and Critical Thinking Skills - Ni Nengah Hardiyanti; Luh Putu Artini; Dewa Putu Ramendra (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was conducted to investigate the impact of integrating Padlet into the Think-Pair-Share strategy on EFL senior high school students’ reading comprehension and critical thinking skills. A pre-experimental design employing a one-group pretest-posttest approach was used in this study. The participants consisted of 36 tenth-grade students selected from one intact class at a senior high school in Bali. Data were collected through a pretest and a posttest and analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics. The findings revealed that the mean posttest score (82.19) was higher than the mean pretest score (62.47). Furthermore, the paired-samples t-test indicated a statistically significant difference between the pretest and posttest scores (Sig. (2-tailed) = .000 < .05). These findings suggest that the implementation of Padlet-integrated Think-Pair-Share was associated with improvements in students’ reading comprehension and critical thinking skills. However, because the study employed a one-group pretest-posttest design without a control group, the findings should be interpreted with caution, and the observed improvements cannot be attributed solely to the treatment. Future studies employing more rigorous experimental designs with control groups are recommended to provide stronger evidence regarding the effectiveness of this instructional approach.